2021
DOI: 10.1002/hbe2.280
|View full text |Cite
|
Sign up to set email alerts
|

The digital social partner: Preschool children display stronger imitative tendency in screen‐based than live learning

Abstract: We report on a study in which 4-to 6-year-olds were presented with a stickerretrieval task and asked to choose between one of two tools they could use to complete it. One of the tools was efficient but verbally identified to be the one that "nobody" uses; the other option was less efficient, but children were told it was the tool that "everybody" uses. Children learned about the level of efficiency and normative-use of each tool option through one of three presentation mediums: (i) in a face-to-face, live demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The null results reported in this study, coupled with the recent meta-analysis conducted by Strouse and Sampson (2021) suggests that the video deficit may be a historical phenomenon, specifically, one that changes with the rise in use of and exposure to technology in each society and culture (Fong, Imuta, et al, 2021;Nielsen et al, 2021). The research conducted here as well as most of the research conducted on the video deficit has been done in WEIRD societies.…”
Section: Constraints On Generalitymentioning
confidence: 45%
“…The null results reported in this study, coupled with the recent meta-analysis conducted by Strouse and Sampson (2021) suggests that the video deficit may be a historical phenomenon, specifically, one that changes with the rise in use of and exposure to technology in each society and culture (Fong, Imuta, et al, 2021;Nielsen et al, 2021). The research conducted here as well as most of the research conducted on the video deficit has been done in WEIRD societies.…”
Section: Constraints On Generalitymentioning
confidence: 45%
“…Many social learning paradigms (including some cited in sect. 2.4.1) do not include causally opaque actions, but examine how children process the interplay between conventional and instrumental factors by manipulating effectiveness/optimality of the modeled approach (e.g., Dickerson, Gerhardstein, Zack, & Barr, 2012;Fong, Imuta, Redshaw, & Nielsen, 2021a, 2021b, 2021cLiszkai-Peres, Kampis, & Király, 2021;Schillaci & Kelemen, 2014), prior experience (Williamson, Meltzoff, & Markman, 2008), agent (Fong, Sommer, Redshaw, Kang, & Nielsen, 2021c;Sommer, Redshaw, Slaughter, Wiles, & Nielsen, 2021), presentation medium (Fong et al, 2021a;Strouse & Troseth, 2008), or time pressure (Fong, Imuta, Redshaw, & Nielsen, 2021b). Children's performance in these studies can be interpreted using the BST, yet we cannot assume social and cognitive mechanisms discovered in overimitation studies to be generalizable to these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one study of preschool children found that they were keen to employ ineffective behaviors suggested via a demonstration video while remaining immune to such suggestions when demonstrated in face to face interactions. This may indicate that children transfer their previous experience with digital media as trustworthy and interpret information from digital devices as credible [ 95 ]. Fortunately, studies show that children display the ability to evaluate incoming information both from live and digital sources, based on previous inaccuracy.…”
Section: Emotional and Social Developmentmentioning
confidence: 99%